A Review of Measles Outbreak Cost Estimates From the United States in the Postelimination Era (2004–2017): Estimates by Perspective and Cost Type. (22nd January 2020) - Pike, Jamison; Leidner, Andrew J; Gastañaduy, Paul A
Abstract: Despite the elimination of measles in the United States (US) in the year 2000, cases continue to occur, with measles outbreaks having occurred in various jurisdictions in the US in 2018 and 2019. Understanding the cost associated with measles outbreaks can inform cost-of-illness and cost-effectiveness studies of measles and measles prevention. We performed a literature review and identified 10 published studies from 2001 through 2018 that presented cost estimates from 11 measles outbreaks. The median total cost per measles outbreak was $152 308 (range, $9862–$1 063 936); the median cost per case was $32 805 (range, $7396–$76 154) and the median cost per contact was $223 (range, $81–$746). There were limited data on direct and indirect costs associated with measles. These findings highlight how costly measles outbreaks can be, the value of this information for public health department budgeting, and the importance of more broadly documenting the cost of measles outbreaks. Abstract : Our review of 10 studies presenting cost estimates for 11 measles outbreaks during the postelimination era found that measles can be extremely costly to public health and healthcare institutions in the United States.